The Influence of School Environment On Children's Character Formation in PKN Subjects - Nuraeni, Andi; Utami , Sukma (oneamd.com, 2025)
The school environment is a place or container for children to be guided in all aspects, morals, knowledge, and skills are very important things to be fostered in the school environment. This study aims to determine the factors in the school environment that can shape children's character, especially in the subject of PKN. This study uses the Qualitative Descriptive method by selecting class V SDN 77 Kanaeng Takalar Regency as a sample and 2 informants who are considered to have knowledge and information about the problem. Data collected using instruments in the form of: Observation and Documentation, as well as in-depth interviews with informants. The data was analyzed qualitatively. The results of this study show quite good results in the Influence of the School Environment on the Formation of Children's Character by interviewing informants seen from the aspects of the influence of educators, students, canteens, classrooms and playgrounds, while educators and students both have positive and negative influences on the formation of children's character.